Improving the operational characteristics of electrical power systems of marine vessels - A. E. Savenko; P. S. Savenko (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Consider the experience of use and conduct a study of the electrical power systems of sea vessels to determine the possibility of improving their operational characteristics. Obtain data on noise and vibration levels of electrical power systems elements.METHODS. The article analyzes the electrical power systems of the Azipod type steering columns of the Baltika icebreaker. The issue of regulating the rotation speed of propulsion electric motors using frequency control based on a DC link and parallel-connected inverter units on IGBT transistors is considered. Motor control on the frequency converter side can be based on direct torque control, scalar and vector control. There are control modes for reducing and increasing voltage.RESULTS. Typical dependences of structure-borne noise levels of main engines and generators are given. Measurements were taken at various frequencies of engine sound power levels, exhaust gases and vibration of generator sets. Experimental oscillograms of studies of the parallel operation of diesel generator sets were obtained, on which power exchange and common-mode oscillations were recorded.CONCLUSION. It is proposed to use multiphase AC electric motors to improve performance characteristics, including reducing noise and vibration. The existing experience in using frequency converters based on a rectifier section and inverter units in electric rowing installations with Azipod propellers makes it possible to implement such a change. To do this, it is necessary to parallelize the inverters that supply each of the three phases and provide the appropriate phase shifts.